Active fault-tolerant control for vertical tail damaged aircraft with dissimilar redundant actuation system using integral sliding mode control. (April 2019) - Ijaz, Salman; Hamayun, Mirza T; Yan, Lin; Shi, Cun
The research about the dissimilar redundant actuation system has indicated the potential fault-tolerant capability in modern aircraft. This paper proposed a new design methodology to achieve fault-tolerant control of an aircraft equipped with dissimilar actuators and is suffered from vertical tail damage. The proposed design is based on the concept of online control allocation to redistribute the control signals among healthy actuators and integral sliding mode controller is designed to achieve the closed-loop stability in the presence of both component and actuator faults. To cope with severe damage condition, the aircraft is equipped with dissimilar actuators (hydraulic and electrohydraulic actuators). In this paper, the performance degradation due to slower dynamics of electrohydraulic actuator is taken in account. Therefore, the feed-forward compensator is designed for electrohydraulic actuator based on fractional-order control strategy. In case of failure of hydraulic actuator subject to severe damage of vertical tail, an active switching mechanism is developed based on the information of fault estimation unit. Additionally, a severe type of actuator failure so-called actuator saturation or actuator lock in place is also taken into account in this work. The proposed strategy is compared with the existing control strategies in the literature. Simulation results indicate the dominant performance of the proposed scheme. Moreover, the proposed controller is found robust with a certain level of mismatch between the actuator effectiveness level and its estimate.